Systematical overview of google lens efficiency during stem classes - Shapovalov, Yevhenii; Bilyk, Zhanna; Shapovalov, Viktor (My University, 2021)
To develop the structure of the STEM-based ontology cube using CIT Polyhedron, the generally accepted statements about STEM and STEAM approaches were used. Modules of the editor and ontology tools of CIT Polyhedron system were used to generate ontologies, af- ter which the generated ontological graph was visualized by generating an ontological cube. The efficiency of such sturucturization was proved before.
Keywords: STEM; systemize; education; систематизація; освіта